Hi asked in Science & MathematicsMathematics · 1 month ago

# How do you solve for x in: ln(3)=ln(10)-(0.1)(x)?

Relevance
• 1 month ago

Solve just like any equation:

ln(3) = ln(10) - (0.1)(x)

-0.1x = [ln(3) - ln(10)]

x = [ln(3) - ln(10)] / -0.1 = 12.03972804

• stanschim
Lv 7
1 month agoReport

I simply subtracted ln(10) from each side and wrote the equation with the terms reversed from the original problem.  Remember, try to isolate the unknown, x, on the left side of the equation when doing algebra.

• Philip
Lv 6
1 month ago

ln(3) = ln(10) - (0.1)x, ie. ln(10) - ln(3) = ln(10/3) = (0.1)x. Multiply through

bt 10 getting x = 10ln(10/3) = 10(1.203972804) = 12.0397804.

• Vaman
Lv 7
1 month ago

ln(3)=ln(10)-(0.1)(x)?

0.1x = ln 10 -ln 3=ln 10/3

10/3= e^(0.1x) =e^(x/10)

x = 10 ln(10/3)=12.04

• ?
Lv 7
1 month ago

ln(3) =  ln(10) - (0.1)(x) ⇒

0.1x = ln 10 - ln 3

.......ln 10 - ln 3

x = ---------------

............0.1

......2.30259 - 1.09861

x = ------------------------

............0.1

x = 12.0398......................ANS